Physicochemical Properties and Sensory Evaluation of Cracker Incorporated with Green Spinach (Spinacia oleracea) and Red Spinach (Amaranthus dubius) during Storage - Daphane Teo Wen Xin (2019)
Incorporating spinach powder can be seen as a commodity to increase the nutritional value, physical properties and creating new flavour of cracker. The purpose of this study was to develop a new food product and determine the physicochemical properties and sensory acceptability of cracker incorporated with various concentrations of green spinach and red spinach powder. Shelf life study was conducted by observing the texture and colour properties during four weeks of storage. Overall texture analysis that was conducted by using texture analyzer can be concluded by saying that hardness and fracturability of cracker showed increasing progression with increasing concentration of spinach powder but showed decreasing trend with time. Chromatic parameters (L*, a*, b*) of colour properties that was conducted using chromameter showed decreasing progression with increasing percentage of flour substitution and showed decreasing trend with time. For proximate analysis, the result indicated that with the increasing concentration of spinach powder, the values for proximate analysis decreases for moisture but increases for ash, fat and protein content. The sensory evaluation conducted among 40 panelists showed higher interest in red spinach cracker with 5% flour substitution. The effect of flour substitution with spinach powder was positive in terms of decreasing moisture content and increasing ash, fat and protein content. Along with the higher acceptance of the cracker incorporated with spinach powder, the objectives of the study were achieved.